Swapping structural determinants of ribonucleases: an energetic analysis of the hinge peptide 16-22. - Mazzarella, L (National Academy of Sciences, 1995)
Bovine seminal ribonuclease (BS-RNase) is a homodimeric enzyme strictly homologous to the pancreatic ribonuclease (RNase A). Native BS-RNase is an equilibrium mixture of two distinct dimers differing in the interchange of the N-terminal segments and in their biological properties. The loop 16-22 plays a fundamental role on the relative stability of the two isomers. Both the primary and tertiary structures of the RNase A differ substantially from those of the seminal ribonuclease in the loop region 16-22. To analyze the possible stable conformations of this loop in both enzymes, structure predictions have been attempted, according to a procedure described by Palmer and Scheraga [Palmer, K. A. & Scheraga, H. A. (1992) J. Comput. Chem. 13, 329-350]. Results compare well with experimental x-ray structures and clarify the structural determinants that are responsible for the swapping of the N-terminal domains and for the peculiar properties of BS-RNase. Minimal modifications of RNase A sequence needed to form a stable swapped dimer are also predicted.